Preferential interaction of the Alzheimer peptide Aβ‐(1–42) with Omega‐3‐containing lipid bilayers: structure and interaction studies. Issue 4 (17th February 2016) - Emendato, Alessandro; Spadaccini, Roberta; De Santis, Augusta; Guerrini, Remo; D'Errico, Gerardino; Picone, Delia
Abstract : Many age‐related neurodegenerative diseases, including Alzheimer Disease (AD), are elicited by an interplay of genetic, environmental, and dietary factors. Food rich in Omega‐3 phospholipids seems to reduce the AD incidence. To investigate the molecular basis of this beneficial effect, we have investigated by CD and ESR studies the interaction between the Alzheimer peptide Aβ‐(1–42) and biomimetic lipid bilayers. The inclusion of 1, 2‐didocosahexaenoyl‐sn‐glycero‐3‐phosphocholine does not change significantly the bilayers organization, but favors its Aβ‐(1–42) interaction. The Omega‐3 lipid amount modulates the effect intensity, suggesting a peptide selectivity for membranes containing polyunsatured fatty acids (PUFA) and providing hints for the mechanism and therapy of AD. Abstract :